The Linux Enterprise Cluster, Karl Kopper : No Starch Press, 2005 - Grosclaude, Eduardo (2006)
This book focuses on Load Balance and High Availability clustering, clearly aiming at the practitioner. It intends to help a technical user design, build and maintain clustered services from the ground up. Theory on clusters and High Availability is skimmed through or not presented at all. However, the book makes for a complete and useful manual on tools and techniques commonly used in the domain. High Performance clustering, on the other hand, falls out of scope.